Sinergitas Peran Guru dan Orang Tua Dalam Meningkatkan Kedisiplinan Siswa Melalui Mata Pelajaran Akidah Akhlak Kelas III MIN 1 Kota Mataram - Nafisah; Sobry, M; Khairul Huda (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
The background of this research is the researcher's attention to the synergy of the role of teachers and parents in increasing student discipline through the subject of moral ethics class III Min 1 Mataram City in the 2022/2023 academic year. This research uses a qualitative approach with a descriptive type. The data sources used in this study were teachers and parents of students at MIN 1 Mataram City. The techniques used in this study are observation, interviews and documentation. The data analysis techniques used in this study are data reduction, data presentation, and conclusions/verification. Meanwhile, to check the validity of the data, researchers used triangulation, used reference materials, and checked. The results of this study indicate that, the synergy of the roles of teachers and parents in improving student discipline through the subject of aqidah morals, namely (1) The synergy of the roles of teachers and parents is carried out with good, innovative and creative communication patterns of teachers in increasing student discipline as a proactive step to communicate with parents. (2) The form of teacher and parent synergy is by holding a meeting with parents on the day of accepting new students, making correspondence between teachers and parents, having consultations when receiving report cards, holding school celebrations or meeting students' work, there is liaison book, hold regular teacher and parent student meetings, then the teacher informs the homeroom teacher to be conveyed to the watsap group with the guardian parent if unwanted things happen or problems occur with students.